IMPACT OF CYPERMETHRIN (25%EC) ON FREE AMINO ACIDS AND PROTEASE ACTIVITY LEVELS IN THE FRESHWATER FISH CIRRHINUS MRIGALA (HAM.) - P. NEELIMA,; L. CYRIL ARUN KUMAR,; J.CHANDRA SEKHARA RAO,; N. GOPALA RAO, (The Bioscan, 2011)
Cypermethrin is a synthetic pyrethroid (SP) insecticide employed all over the world to control different pests of crops and fishes because of its low mammalian toxicity, degradability and persistence nature. Acute toxicity experiments were conducted to the fish Cirrhinus mrigala (Ham.) for the toxicant cypermethrin. Sub-lethal concentrations of 5, 10, 15 and 20% 96hr LC50 were prepared and exposed the fish, Cirrhinus mrigala for 2, 4, 6 and 8 days for 96 hr to assess LC50. Gill, liver and muscle tissues were dissected out at end of each day and free amino acids and protease activity was estimated. Dose as well as exposure period depended (p≥0.05) increase in the free amino acid levels and protease activity was observed. Maximum elevation of free amino acids and protease activity was observed in liver, followed by muscle and gill.